Cytochrome P450 complement (CYPome) of Candida oregonensis, a gut-associated yeast of bark beetle, Dendroctonus rhizophagus. Issue 9 (September 2016) - Hernández-Martínez, Fabiola; Briones-Roblero, Carlos Iván; Nelson, David R.; Rivera-Orduña, Flor Nohemí; Zúñiga, Gerardo
Abstract: Bark beetles (Curculionidae: Scolytinae) and associated microorganisms must overcome a complex tree's defence system, which includes toxic monoterpenes, to successfully complete their life cycle. A number of studies have suggested these microorganisms could have ecological roles related with the nutrition, detoxification, and semiochemical production. In particular, in filamentous fungi symbionts, cytochrome P450 (CYP) have been involved with terpenoid detoxification and biotransformation processes. Candida oregonensis has been isolated from the gut, ovaries, and frass of different bark beetle species, and it is a dominant species in the Dendroctonus rhizophagus gut. In this study, we identify, characterise, and infer the phylogenetic relationships of C. oregonensis CYP genes. The results indicate that the cytochrome P450 complement (CYPome) is composed of nine genes (CYP51F1, CYP61A1, CYP56D1, CYP52A59, CYP52A60, CYP52A61, CYP52A62, CYP5217A8, and CYP5217B1), which might participate in primary metabolic reactions such as sterol biosynthesis, biodegradation of xenobiotic, and resistance to environmental stress. The prediction of the cellular location suggests that these CYPs to be anchored to the plasma membrane, membranes of the endoplasmic reticulum, mitochondria, and peroxisomes. These findings lay the foundation for future studies about the functional role of P450s, not only for yeasts, but also for the insects with which they interact. Graphical abstract: Highlights: C. oregonensis CYPome is comprised by nine cytochrome P450. CYPome includes CYP51, CYP61, and CYP56, involved in primary metabolism. CYP56 is flanked by MFS instead of DIT1 . CYP52 family might be involved in host terpenes detoxification. CYP52A62 is part of a cluster relationship with secondary metabolism.